Developing New Platforms for Performance Practice in Contemporary Thailand: Performance-Making and Performance Research as Intertwined Creative Processes - Damrhung, Pornrat (Journal of Fine and Applied Arts Khon Kaen University, 2022)
This article examines a new approach about performance practice in contemporary Thailand. This new approach emerged from a performance research platform that involved eight different performance projects between 2017 and 2020. Each performance project paired artists from different backgrounds and specialties with one another, and challenged them to work together on a single new piece. This cross-disciplinary concept challenge sought to move the artists and theatre scholars out of their comfort zones and to get them to ask questions about key aspects of and new possibilities for their artistic practice and to consider new ways to connect up with other artists and performers. This approach stressed that the working process for each collaborative performance emerged out of a creative problem that the artists needed to solve in two key interconnected processes: performance-making and performance research. Opinions are reflected as part of the assessment in order to meet the research objectives. The process innovated Thai contemporary performance works is outstanding and difference because it is a contemporary performance that let the Thai wisdom as the lead and also wove into it western knowledge to support the creative working process. The research platform developed here was an experimental space for nurturing the arts, performance research activities, and new artist-researchers who produced them. The results of this experimentation continue the spirit of Thai research, but infuses it will contemporary modes of working and communicating between art forms and generations. This ensures that diverse ideas and cultural forms are given a place in today’s society. It is a new Thai work that is different from the original roots.